Molecular cloning of full-length haemagglutinin (H5HA) gene of highly pathogenic avian influenza virus (HPAI) H5N1 - Abubakar, Mustapha Bala; Ideris, Aini; Omar, Abdul Rahman; Bejo, Mohd Hair (2009)
Avian Influenza viruses belonging to the Orthomyxoviridae family are enveloped viruses with segmented negative sense RNA genome surrounded by a helical symmetry capsid. Influenza viruses, especially the highly pathogenic avian influenza virus (HPAI) such as H5 or H7 subtype are the most important pathogens for the poultry industry in recent times. The haemagglutinin protein and neuraminidase, serves as the target for the immune response of the host. Due to recurrent genetic reassortments between avian and human influenza viruses, global pandemics may emerge and the naive human immunity could not withstand pressure by the novel hybrid virus. The emergence of genetic engineering technology provided the industry with new methods of manufacturing diagnostics tools and vaccines. After extraction of RNA from the cell culture of strain influenza A/Chicken/Malaysia/2004(H5N1) of AIV, the viral RNA was converted to cDNA by a specific primer. The cDNA was amplified by the polymerase chain reaction (PCR) and analyzed by agarose gel electrophoresis. The intact PCR product of full length haemagglutinin gene was cloned in TOPOTM TA Cloning vector. The full-length HA-encoding gene of H5N1 AIV was subcloned into a pPICZA vector. After successful ligation, the constructed plasmid was transformed into E.coli.Top10, Plasmid DNA from transformed bacteria was extracted in white colony and positive clones were confirmed by restriction digestion with Sacl and Not1 restriction enzymes, colony PCR screening and nucleotide sequencing. Construction of a recombinant pPICZA/H5HA plasmid containing the full length haemagglutinin gene was achieved as a first step towards the expression in Pichia pastoris.